Measurement of pH and calcium ions release from different calcium hydroxide pastes at different intervals of time: Atomic spectrophotometric analysis - Pranab Misra; Rhythm Bains; Kapil Loomba; Abhinav Singh; V.P. Sharma; R.C. Murthy; Rakesh Kumar (Elsevier, 2017)
Aim: To evaluate the effect of different vehicles on pH and release of calcium ions from calcium hydroxide (CH) paste from apical third of root canals. Methods: 40 single rooted extracted human mandibular premolars were instrumented with RevoS files (MicroMega) up to ISO size 40. The teeth were divided into 4 groups on the basis of vehicle as follows: Group I - calcium hydroxide mixed with 2% chlorhexidine; Group II - calcium hydroxide mixed with propylene glycol; Group III - calcium hydroxide mixed with glycerine; and Control - calcium hydroxide mixed with double distilled water. Each group had two subgroups (n = 5) on the basis of the calcium hydroxide delivery. Subgroup A - calcium hydroxide paste placed with spiral filler (Lentulospiral) subgroup B - calcium hydroxide paste placed with flat wire filler (Paste Inject). pH and calcium ion release was evaluated at 24 h, 48 h, 7th day, 15th day and 30th day using a pH meter and atomic absorption spectrophotometer respectively. Results: The calcium release from various groups was highest for CH+glycerine (Group III) followed by CH+chlorhexidine (Group I), CH+propylene glycol (Group II) and CH+double distilled water (control). At all the intervals the differences in calcium ion release among the groups were statistically significant (p < 0.05), except on day 7. Delivery technique did not have a significant effect on calcium ion release. Highest pH values were recorded from CH+glycerine group at day 30 for both the delivery systems, however rise in pH from day 1 to day 30 were non-significant in all groups with both delivery systems. Conclusion: Demonstrable changes in calcium ion release occurred from the calcium hydroxide mixed with various vehicles and CH+glycerine group showed the maximum calcium ion release at all intervals and highest pH day 30.